Effect of think-pair-share technique on academic performance of office practice students in colleges of education Kwara state - Ademiluyi, Lawrence F.; Fawale, Afiss Adebayo (Journal of Education in Black Sea Region, 2022)
The study aimed at investigating the effect of the think-pair-share technique on academic performance of students in office practice in colleges of education, Kwara state, Nigeria. One intact group was selected as the control group and the other as the experimental group at random. The study was directed by two research questions and two null hypotheses. The study used a quasi-experimental approach that included pre- and post-tests. The population of the study comprised 125 students majoring in business. The purposive sampling procedure was used in selecting 125 students who were grouped into treatment and control groups. The instruments for data collection were programmed material (modules) for office practice and Office Practice Achievement Test (OPAT) developed by the researchers based on the topic to be covered. Two hypotheses with significance levels of .05 were tested using the ANCOVA statistic technique. Both groups had 15 reading sessions; the experimental group received treatment and had their reading instruction based on the think-pair-share technique, whereas the control group received reading instruction using the traditional approach. The findings suggested that using the think-pairshare method can improve students’ academic performance.